Multiphase pyrolysis of waste expanded polystyrene and in-situ hydrogenation of pyrolysis oil on silica-alumina supported nickel catalyst for the production of fuel range paraffinic and aromatic hydrocarbons - Verma A.; Pramanik H. (My University, 2025)
In this work, thermal and catalytic pyrolysis of waste expanded polystyrene (WEPS) have been investigated in a laboratory designed semi-batch reactor in the temperature range of 400-700℃ and heating rate of 15 ℃/min to produce gasoline range lower paraffins and valuable aromatics i.e., benzene, toluene and ethylbenzene (BTE). Three different type of reactor arrangements i.e., liquid phase/A-type, vapour phase/B-type and multiphase/AB-type have been used to conduct the catalytic pyrolysis of WEPS using nickel on silica-alumina catalyst. The thermal pyrolysis of WEPS produced highest liquid yield of 94.37 wt.% at a temperature of 650℃ and heating rate of 15 ℃/min, whereas, liquid phase/A-type, vapour phase/B-type and multiphase/AB-type catalytic pyrolysis produced highest liquid yield of 88.54 wt.%, 83.21 wt.%, and 81.15 wt.%, respectively, at the same heating rate of 15o C/min and at the temperature of 600℃, 550℃, and 550℃, respectively. The pyrolysis oil obtained from thermal pyrolysis mainly contains styrene monomer of 84.74 wt.% and very less BTE content of 11.38 wt.%. Among, the all types of catalytic pyrolysis, AB-type/multiphase pyrolysis produced pyrolysis oil with highest amount of BTE content of 28.56 wt.%. Furthermore, the pyrolysis oil obtained from A-type, B-type and AB-type catalytic pyrolysis contains low styrene content of 69.94 wt.%, 65.67 wt.% and 55.55 wt.%, respectively, as compared to thermal pyrolysis (84.74 wt.%). © 2023, National Institute of Science Communication and Policy Research. All rights reserved.